A Regional Study of The History of The Muslim Minority In Singapore (1965-1990) - Nuraidah, Syifa; Fauzan, Rizal (Jurnal Kawasan Sejarah, 2023)
This research aims to examine the historical area of Muslim minorities in Singapore during the period 1965 to 1990. Singapore is a multicultural country with a majority Buddhist, Christian and Taoist population, but also has a significant Muslim community. Despite being in a non-Muslim majority, the minority Muslim community has contributed substantially to the country's social, political and economic history. In this study, the author uses a holistic and multidisciplinary historical approach to understand the dynamics of the Muslim minority historical region. Data and primary sources were collected from historical archives, academic literature, and interviews with historical witnesses who had direct experience of the research period. This paper describes the development of the Muslim minority historical region in Singapore during the period 1965-1990, including the factors that influenced social and cultural changes in the community. It also considers the role of the government and religious institutions in promoting social integration between minority and majority Muslims. The results show that the minority Muslim community has undergone significant changes during the period. Some of the aspects studied include the development of religious institutions, Islamic education, political participation, and interaction with other religious groups. This research provides new insights into the history of Muslim minorities in Singapore and contributes to further understanding of the dynamics of multiculturalism in the country. The results of this research are expected to be an important reference for future historical and social studies.